Nutrient alginate encapsulation of nodal segments of Althaea officinalis L., for short-term conservation and germplasm exchange. (2nd November 2018) - Naz, Ruphi; Anis, Mohammad; Alatar, Abdulrahman A.; Ahmad, Altaf; Naaz, Afshan
Abstract: In the present study, an alternate method for germplasm storage in the form of artificial seeds was standardized via nodal explants excised from in vitro proliferated shoots. The explants were encapsulated using sodium alginate and calcium chloride as gelling matrix. For development of root along with shoot, excised nodal segments were pretreated with ½ MS medium along with 20 μM IBA for 24 h and encapsulation was carried thereafter. Combination of 3% sodium alginate augmented with 100 mM CaCl2 .2H2 O was found appropriate for the formation of clear and uniform beads and subsequent conversion of encapsulated nodal segments into plantlets. Maximum (66%) encapsulated nodal segments were converted into plantlets on MS medium supplemented with 7.5 μM BA and 0.5 μM NAA after eight weeks. Regeneration frequency of auxin-pretreated encapsulated and non-encapsulated nodal segments (stored at 4 ºC) was evaluated at different storage time (0 to 6 weeks). After four weeks of storage, encapsulated propagules exhibited highest conversion response on the optimized medium after eight weeks of culture. Plantlets were hardened and established with success in ex vitro conditions. Conversion of synthetic seeds into plantlets was observed when these were directly sown in autoclaved Soilrite TM (Keltech Energies, Bangalore, India). Abstract :